Aplikasi Simulasi dan Pembelajaran Routing Protocol dengan metode OSPFv2 Berbasis Android - Agung Triarta Hariyanto; Agus Noertjahyana; Djoni Haryadi Setiabudi (Jurnal Infra, 2017)
When Router want to communicate with another router, they need do some process that well known as routing protocols. OSPFv2 choosen to be the focus of routing protocol methods in this application because, the frequent used of this method in real implementation. Rarely similar application is one of another reason to make this application. So in this thesis made application that featured with display PDF file formatted, show exercise to user, and can do simulation about OSPFv2This application is developed based on android, so user can easily use this application. This application can display file PDF formatted, can show some exercise to user and do evaluation calculation about right or wrong answer, and can do simulation with OSPFv2 method with input from user. Application can be run on Android Jellybean operating system API 18 and so on.The result of this thesis is this application can show PDF file well, and show excersice and do evaluation calculation, and do simulation about OSPFv2 with focus topology in point-to-point and bus multi-access well. Topology input limited by 5x8 box size, and adding PDF file and excersice can only be done by manually input because this application is offline.